COMPARISON OF GRAM-BACTERIAL RESISTANCE PATTERNS OF PNEUMONIA IN THE ELDERLY AND NON-ELDERY - Mahmuda, Iin Novita Nurhidayati; Dewi, Listiana Masyita; Jatmiko, Safari Wahyu; Faizah, Ishmah Nur; Kania, Yulia Intan; Affifah, Fathiyya Noor; Prasetyo, Andri Sugeng (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2024)
Pneumonia is an infectious disease of the lungs caused by various microorganisms that cause inflammation of the lung parenchyma. This infectious disease is more likely to affect elderly patients. Most of the microorganisms that cause pneumonia are bacteria, both gram-positive and gram-negative bacteria. The main management for patients with pneumonia is to use antibiotic therapy. The irrational use of antibiotics can increase the occurrence of antibiotic resistance. This study aimed to compare the resistance patterns of Gram-positive and Gram-negative bacteria causing pneumonia in elderly and non-elderly patients. This study used a descriptive method with secondary data in the form of medical record data and antibiotic sensitivity test data. based on this study, it was found that the bacteria that caused pneumonia were mostly gram-negative bacteria. The most common gram-negative bacteria was Klebsiella pneumoniae, while the most common gram-positive bacteria was Streptococcus sp. The results of antibiotic sensitivity tests on gram-positive bacteria showed that the majority were resistant to fluoroquinolones, namely Ciprofloxacin (64%), Levofloxacin (59%). Meanwhile, gram-negative bacteria were mostly resistant to Ampicilin (84%) and Cefadroxil (83%). Conclusion: The bacteria that cause pneumonia, both gram-positive and gram-negative, experienced antibiotic resistance to the tested antibiotics. The selection of antibiotic therapy can be adjusted according to the causative bacteria and their resistance patterns.Keywords: Pneumonia; Antibiotic resistance pattern; Gram-positive bacteria; Gram-negative bacteria